2020
DOI: 10.1016/j.devcel.2020.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-Derived H2O2 Promotes Symmetry Breaking of the C. elegans Zygote

Abstract: Highlights d Mitochondria promote symmetry breaking through a local increase in cortical H 2 O 2 d Both maternal and sperm mitochondrial H 2 O 2 contribute to symmetry breaking d Artificial cortical trapping of mitochondria is sufficient for symmetry breaking

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…These studies and the molecular degeneracy of the actomyosin cortex [120,122] (discussed below) indicate that the polarization of the zygote most likely relies on the timely and spatial coordination of multiple molecular processes. This is further exemplified by a recent finding from De Henau et al [137], who have reported a novel mechanism/requirement for symmetry breaking. Here, high levels of H 2 O 2 , released from a polarized mitochondrial network, can drive posteriorization of the zygote.…”
Section: (A) Aurora a Regulates Actomyosin Flow And Ensures A Monopolar Antero-posterior Axismentioning
confidence: 59%
“…These studies and the molecular degeneracy of the actomyosin cortex [120,122] (discussed below) indicate that the polarization of the zygote most likely relies on the timely and spatial coordination of multiple molecular processes. This is further exemplified by a recent finding from De Henau et al [137], who have reported a novel mechanism/requirement for symmetry breaking. Here, high levels of H 2 O 2 , released from a polarized mitochondrial network, can drive posteriorization of the zygote.…”
Section: (A) Aurora a Regulates Actomyosin Flow And Ensures A Monopolar Antero-posterior Axismentioning
confidence: 59%
“…In addition, the polar distribution of zygotic mitochondria may support cell polarization and axis formation, like in the C. elegans zygote, the mitochondria of which produce a local increase of hydrogen peroxide (H 2 O 2 ), thus disrupting cell symmetry and forming the anterior-posterior axis (De Henau et al, 2020). In Arabidopsis, H 2 O 2 and calcium are the key molecules leading to polar cell growth in the pollen tube, and recent work showed that mitochondrial calcium uniporter, MCU1/2, is required to support pollen tube elongation (Selles et al, 2018).…”
Section: What Are the Roles Of Mitochondrial Dynamics In The Zygote?mentioning
confidence: 99%
“…[ 29,30 ] An asymmetric mitochondrial distribution has been described in the oocytes of many other species, including arthropods, ascidians, and vertebrates, [ 28 ] and has been linked to hydrogen peroxide production during the polarization of Caenorhabditis elegans zygotes. [ 31 ] It is unknown whether intrinsic redox gradients or differential activation of HIF modulates the early axial patterning of other animals as well.…”
Section: Hif Pathways Regulate Multiple Steps Of Metazoan Developmentmentioning
confidence: 99%